An analysis of the ability of small urban wetlands to treat stormwater: the case of Princess Vlei wetland, Cape Town - Underhill, Laura (Department of Environmental and Geographical Science, 2018)
The consequences of poor water quality on urban aquatic ecosystems have been well established by researchers worldwide. Stormwater management in the urban areas of South Africa predominately focuses on the collection and diversion of runoff into the nearest receiving water body, with little acknowledgement of the impacts on the environment. The City of Cape Town Metropolitan municipality is an authoritative entity on Cape Town pollution and has acknowledged that polluted stormwater is a significant contributor to the deterioration of its' urban aquatic ecosystems due to the persistence of conventional drainage systems. Small urban wetlands are often overwhelmed by the quality of stormwater and urban runoff. Thus water bodies receiving urban stormwater runoff often have elevated loadings of pollutants. In theory wetlands are capable of treating these pollutants and improving water quality through various ecosystem services, but understanding the performance of wetlands under varying conditions is difficult to determine. In South Africa, there is a paucity of studies focussing on the impacts of urban development on small, urban wetlands and thus their ability to provide ecosystem services. This study aimed to identify the surface water quality of Princess Vlei, a small urban wetland, over the past 8 years, and establish the ingress and outflow of the wetland. The pollutant concentrations within the wetland were best explained by the predictor variables of total rainfall and progression of time. Impacts of total rainfall differed with various parameters resulting in larger volumes of water entering the wetland either diluting pollutant concentrations or elevating pollutant concentrations. These inverse trends were proved through the significant correlations found between total rainfall and COD and total rainfall and EC, while the variable of time influenced the wetland's ability to provide ecosystem services, either through the accumulation, retention or flushing of pollutants. The accumulation of pollutants over time was identified through the increasing concentrations off COD and PO₄³⁻, with the exception of NH₃-N that decreased over time. This implies that the wetland was able to assimilate the NH₃-N but not the COD and PO₄³⁻. The results did not suggest that the wetland was able to treat the water, as the literature emphasises, rather, confirmed the pervasive impacts of the urban catchment on the ability of ecosystem services to treat water quality in the wetland.